Current status the EDEN ISS – An Antarctic greenhouse to enhance plant cultivation in space - Zabel, Paul; Bamsey, Matthew; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Romberg, Oliver (2016)
EDEN ISS is a European project to enhance plant cultivation technologies for future crewed exploration missions and for the International Space Station. The project began in March 2015 and is co-funded by the European Union. The project consortium consists of 13 organizations from 6 countries in Europe and Canada. This presentations describes the current status of the project. This includes detailed information about the design of the Antarctic greenhouse facility and its subsystems. Furthermore, the operational and scientific planning of the Antarctic analogue mission are explained. An outlook on the upcoming steps of the project will be given too.